Simulating Observations of Southern Ocean Clouds and Implications for Climate. Issue 21 (29th October 2020) - Gettelman, A.; Bardeen, C. G.; McCluskey, C. S.; Järvinen, E.; Stith, J.; Bretherton, C.; McFarquhar, G.; Twohy, C.; D'Alessandro, J.; Wu, W.
Abstract: Southern Ocean (S. Ocean) clouds are important for climate prediction. Yet previous global climate models failed to accurately represent cloud phase distributions in this observation‐sparse region. In this study, data from the Southern Ocean Clouds, Radiation, Aerosol, Transport Experimental Study (SOCRATES) experiment is compared to constrained simulations from a global climate model (the Community Atmosphere Model, CAM). Nudged versions of CAM are found to reproduce many of the features of detailed in situ observations, such as cloud location, cloud phase, and boundary layer structure. The simulation in CAM6 has improved its representation of S. Ocean clouds with adjustments to the ice nucleation and cloud microphysics schemes that permit more supercooled liquid. Comparisons between modeled and observed hydrometeor size distributions suggest that the modeled hydrometeor size distributions represent the dual peaked shape and form of observed distributions, which is remarkable given the scale difference between model and observations. Comparison to satellite observations of cloud physics is difficult due to model assumptions that do not match retrieval assumptions. Some biases in the model's representation of S. Ocean clouds and aerosols remain, but the detailed cloud physical parameterization provides a basis for process level improvement and direct comparisons to observations. This is crucial because cloud feedbacks and climate sensitivity are sensitive to the representation of S. Ocean clouds. Plain Language Summary: Clouds over the Southern Ocean are important for climate prediction and may influence the evolution of global temperatures. Thus, these clouds are important to represent properly in models; however, recent studies have revealed models inadequately represent Southern Ocean cloud occurrence and phase, which drive large biases in radiation and subsequent climate sensitivity. Observations from research aircraft over the Southern Ocean south of Australia are compared to simulations with a global climate model which is "nudged" to reproduce the day‐to‐day cloud systems which are sampled. Despite being a coarse horizontal and vertical resolution, the model is able to reproduce many details of cloud phase and water content during the flights. However, the model has some biases, and these observations have been used to improve the model to better represent cloud phase. These results point to specific observational constraints for improving model simulations. Key Points: New model simulations have increased supercooled liquid clouds over the Southern Ocean A nudged GCM can qualitatively reproduce detailed in situ aircraft observations, including size distributions and water contents Detailed comparisons with in situ observations provide better understanding of process biases